International Political Economy (IPE) and Major Agenda of Least Developed Countries(LDCs) in World Trade Organization(WTO) - Gyawali, Toya Narayan (Prashasan: The Nepalese Journal of Public Administration, 2021)
International trade is one of the major discourses of international political economy. Under the WTO framework, issues of LDCs are under the regular negotiation process. These days, trade, investment and economic development are getting much attention in the scope of international political economy. The WTO recognizes the least-developed countries, as per the designation by the United Nations. There are currently forty six least-developed countries as per the UN list, in which thirty five are WTO members and eight countries are in negotiation process for the accession. LDCs have exclusive access to certain international support measures particularly in the areas of development assistance and trade. The benefit of joining the WTO differs from country to country and mostly depends on the role of political economy. The common perception is that, the agenda of LDCs in the WTO are not getting proper attention in the negotiation of multilateral trading system. Some of the decisions and agreements are still in the process of implementation. This paper deals with the major agenda of LDCs in WTO in the context of Nepal. Since the government of Nepal has already decided for the LDC graduation, the review and analysis of the agendas are instrumental in order to analyze the possible impact of multilateral trade in our development endeavor.